Lecture Notes in Physics
DOI: 10.1007/bfb0102246
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the visual light curve of CAL 87

Abstract: We model the visual light curve of CAL 87 based on the assumption that an accreting steadily burning white dwarf irradiates the accretion disk and the secondary star, as suggested by van den Heuvel et al. (1992). We use constraints on the geometry derived from the known orbital period. As sources of visual light we include the secondary star and an accretion disk with an optically thick, cold, clumpy spray at its riml presumably caused by an accretion stream of high mass flow rate impinging on the disk at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
189
1

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(197 citation statements)
references
References 18 publications
7
189
1
Order By: Relevance
“…For details of such models and corresponding parameters see e.g. Schandl & Meyer (1994); Wijers & Pringle (1999); Scott et al (2000); Leahy (2002). It is then natural to assume that the disk is also responsible for the changing pulse profile shape, with the inner edge, precessing with the same period as the outer edge (and all other rings), being the prime candidate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For details of such models and corresponding parameters see e.g. Schandl & Meyer (1994); Wijers & Pringle (1999); Scott et al (2000); Leahy (2002). It is then natural to assume that the disk is also responsible for the changing pulse profile shape, with the inner edge, precessing with the same period as the outer edge (and all other rings), being the prime candidate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to initial conditions (e.g. the relative orientation of neutron star spin and orbital angular momentum at birth of the X-ray binary), the existence of internal forces on the accretion disk, like coronal winds (Schandl & Meyer 1994), radiation pressure (Pringle 1996;Wijers & Pringle 1999), or the impact of the accretion stream (Shakura et al 1999) have been proposed to produce and maintain the observed configuration. 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This modulation is the best evidence for an inclined, precessing, and warped accretion disk in an X-ray binary system. The origin of the warping is not yet fully understood, but may be caused either by radiation driven accretion disk winds (Schandl & Meyer 1994) or by radiation pressure (Maloney & Begelman 1997). The precessing motion of the disk can be understood in the context of tidal interaction and/or as a consequence of non vanishing torques acting on the disk, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Crosa & Boynton (1980) found that the average mass transfer rate to the outer rim of the accretion disk is somewhat larger than that required to maintain the observed X-ray luminosity. In the model of Schandl & Meyer (1994), the disk wind results from irradiation of the disk by the central source. Vrtilek et al (2001) and Boroson et al (2001) found signatures of outflowing gas in the UV spectrum of the system.…”
Section: Evidence For the Coronal Mass Ejectionmentioning
confidence: 99%